2007
DOI: 10.1080/08860220601166545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peritoneal Dialysis Solution Type on Serum Lipid Levels in End-Stage Renal Disease

Abstract: Among the different cardiovascular risk factors, lipid abnormalities dominate the high mortality in chronic ambulatory peritoneal dialysis patients. So far, no data comparing the effect of standard glucose-containing, amino acid-containing, and icodextrin-containing peritoneal dialysis solutions on serum lipid concentrations in a chronic ambulatory peritoneal dialysis population are available. To determine the effect of peritoneal dialysis solutions on parameters of lipid metabolism, 67 subjects who had contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…In their study, Kanbay et al found that serum lipid parameters of solutions with AAs and other solutions administered during peritoneal dialysis did not differ significantly [51]. Contrary to expectations, the current study detected significant decrease in HDL levels of the Nutrineal group, with cholesterol values remaining stable.…”
Section: Discussioncontrasting
confidence: 55%
“…In their study, Kanbay et al found that serum lipid parameters of solutions with AAs and other solutions administered during peritoneal dialysis did not differ significantly [51]. Contrary to expectations, the current study detected significant decrease in HDL levels of the Nutrineal group, with cholesterol values remaining stable.…”
Section: Discussioncontrasting
confidence: 55%
“…It is known that long‐term icodextrin usage has no harmful influence on the peritoneal membrane 32 . Gobin et al.…”
Section: Discussionmentioning
confidence: 99%
“…96 Clinical trials with amino acid-based dialysate have shown mixed results with respect to plasma lipid levels. [97][98][99] The Improved Metabolic Control of Physioneal, Extraneal and Nutrineal (IM-PENDA) and Evaluation of Dianeal, Extraneal and Nutrineal in diabetic PD patients (EDEN) studies demonstrated that PD prescriptions containing amino acid-based dialysate and icodextrin achieved lower serum lipid levels when compared with dextrose-only PD prescriptions. However, the amino acids and icodextrin group also demonstrated higher mortality from congestive heart failure.…”
Section: Hyperlipidemiamentioning
confidence: 99%